Rumination and problematic substance use among individuals with a long-term history of illicit drug use. (1st October 2019) - Memedovic, Sonja; Slade, Tim; Ross, Joanne; Darke, Shane; Mills, Katherine L.; Marel, Christina; Burns, Lucy; Lynskey, Michael; Teesson, Maree
Highlights: Relationship between rumination subtypes and problematic substance use was examined. Focus was on heroin dependence, polydrug use and injection-related health problems. Ruminative brooding was associated with all measures of problematic substance use. Ruminative reflection was not associated with indices of problematic substance use. Ruminative brooding may be an important factor to target in substance use treatments. Abstract: Background: Rumination is a cognitive process that is implicated in the development and maintenance of various forms of psychopathology, including problematic substance use. Most studies on the role of rumination in substance use have been conducted among community samples or individuals with alcohol use disorders and have predominately focused on overall rumination rather than differentiating between its subtypes, ruminative brooding and ruminative reflection. The current study therefore aimed to investigate i) whether rumination subtypes are associated with problematic substance use among people with a long-term history of illicit drug use independently of related psychological disorders (depression and post-traumatic stress disorder [PTSD]), and ii) whether gender moderates these relationships. Methods: This cross-sectional study used data from the Australian Treatment Outcome Study (ATOS); a naturalistic prospective cohort study of people with heroin dependence. At the 11-year follow-up of ATOS, a total of 380 participants completed measures of rumination, depression, PTSD, and indices of problematic substance use. Results: Hierarchical logistic regression analyses indicated that higher brooding scores were associated with current heroin dependence (OR = 1.11, CI: 1.01–1.22), polydrug use (OR = 1.16, CI: 1.06–1.28) and experience of injection related health problems (OR = 1.08, CI: 1.00–1.17), independently of depression, PTSD, and other covariates. Reflection was not related to any of the substance use measures. These results were not moderated by gender. Conclusions: Findings indicate that ruminative brooding is related to a poorer substance use profile among people with long-term illicit drug use and highlight the potential benefits of targeting brooding during substance use treatment.